Functional metabolomics: unlocking the role of small molecular metabolites - Chen, Hetao; Kong, Jiao; Du, Peipei; Wang, Qian; Jiang, Tao; Hou, Xixi; Feng, Tingting; Duan, Jiajia; Liu, Chuanxin (Frontiers in Molecular Biosciences, 2025)
Metabolomics is an expanding field dedicated to elucidating metabolic disorders by analyzing endogenous small molecules in biological samples. With the rapid advancement of metabolomics, researchers are investigating the influence of metabolites on metabolic phenotypes. The emergence of functional metabolomics provides a methodological framework to address this issue. This approach focuses on the biological functions of metabolites and their corresponding enzymes while validating the potential mechanisms of differential metabolites through in vivo and in vitro experiments. Despite numerous research findings, a systematic compilation of case studies remains absent. Therefore, this review systematically summarizes and evaluates functional metabolomics, covering its historical development, current state, and future directions, with the aim of fostering its advancement and offering solutions for further research.